Issues and problems in public management education - Sto. Tomas, Patricia A. (Philippine Journal of Public Administration, 1990)
Public Management education's (PME) negligible impact on the government bureaucracy calls for a reexamination of the PME curriculum. For instance, the "manager syndrome," which is noticeably rampant in the bureaucracy, is also perpetuated by the PME. The academe has to produce more craftsmen by reinforcing the skills aspect of public administration in the fields of accounting, finance, marketing and management.